2018
DOI: 10.1177/2325967118756825
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder MRI Abnormalities in Asymptomatic Little League Baseball Players

Abstract: Background:Youth baseball is extremely popular in the United States, but it has been associated with shoulder pain and injury. The incidence of shoulder abnormalities in this athletic population has yet to be defined.Purpose:To examine abnormalities noted on magnetic resonance imaging (MRI) in the shoulders of asymptomatic Little League baseball players and to correlate these findings with the players’ throwing history and physical examinations.Study Design:Case-control study; Level of evidence, 3.Methods:A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…While most studies implicate overuse in the pathogenesis of these injuries, data are mixed regarding which specific metrics are most critical. This study is in agreement with mounting evidence 2,15,17 that year-round play is particularly harmful to the throwing arms of developing athletes. Erickson et al 2 showed that MLB pitchers from warm-weather climates, which may facilitate year-round play at a young age, were more likely to require UCL reconstruction and required surgery earlier in their careers compared with pitchers from cold-weather climates.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While most studies implicate overuse in the pathogenesis of these injuries, data are mixed regarding which specific metrics are most critical. This study is in agreement with mounting evidence 2,15,17 that year-round play is particularly harmful to the throwing arms of developing athletes. Erickson et al 2 showed that MLB pitchers from warm-weather climates, which may facilitate year-round play at a young age, were more likely to require UCL reconstruction and required surgery earlier in their careers compared with pitchers from cold-weather climates.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, early sport specialization has been shown to predispose young athletes across multiple sports to injury. 1,13,15 While the cause of throwing arm injuries in youth baseball players is undoubtedly multifactorial, continuous year-round play and early single-sport specialization seem to be significant contributors. We believe that serious consideration should be given to modifying the current guidelines for youth baseball players so that a minimum of 3 months of rest is no longer a nonenforced recommendation but a requirement that is enforced, similar to pitch count.…”
Section: Discussionmentioning
confidence: 99%
“…21 In a magnetic resonance imaging study of 23 asymptomatic Little League players, year-round participation in baseball and single-sport participation were associated with abnormal shoulder magnetic resonance imaging findings. 13,24 However, there have been no reports on the prevalence or consequences of sport specialization in large samples of Little League baseball players.…”
mentioning
confidence: 99%
“…There is significant evidence that excessive sport volume is a risk factor for overuse injuries in youth and adolescent athletes. Participating in a single sport for more than 8 months out of the year has been identified as a risk factor in several studies of youth baseball pitchers 11 13,19 as well as in broader samples of youth athletes from different sports. 1,17 Current recommendations suggest that youth athletes should not participate in more hours per week than the athlete’s age.…”
Section: Discussionmentioning
confidence: 99%